A Legal Study on Business Competition in the Field of Financial Sector Technological Innovation and its Challenges - Ramli, Asmarani; Suran Ningsih, Ayup; Puspa Wardhani, Harumsari (Universitas Brawijaya, 2026)
Technological innovation in the financial sector has altered the market structure and the pattern of business competition in Indonesia. Digitalisation through fintech and financial platforms fosters financial efficiency and inclusion, while simultaneously raising new legal issues, such as potential monopoly practices, data dominance, discriminatory algorithms, and market access inequalities. This condition raises the urgency of strengthening the business competition law to respond to the dynamics of the digital economy. Two problems have been formulated for investigation: (1) the legal perspective of business competition against the application of financial sector technological innovation, and (2) the challenge of enforcement of business competition laws against financial technological innovation actors. Given these issues, this study aims to analyse the effectiveness of business competition law in maintaining fair competition in the digital financial sector and to formulate adaptive law enforcement. This study employs a normative- juridical method to support empirical analysis through case studies. The theoretical frameworks used include economic democracy theory, business competition law, and digital market regulation. Research results show that technological innovation in the financial sector escalates the risk of unfair business competition practices that are difficult to address with conventional legal frameworks. Therefore, updating regulations and fostering synergies among authorities are essential to building a fair, inclusive, and sustainable business competition ecosystem.